PENGARUH PENERAPAN MODEL PEMBELAJARAN ARIAS (ASSURANCE, RELEVANCE, INTEREST, ASSESSMENT, SATISFACTION) DALAM SETTING COOPERATIVE TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS VII SEMESTER GENAP SMP NEGERI 1 PADANG CERMIN TAHUN PELAJARAN 2015/2016 - Noviyana, Hesti (LPPM STKIP PGRI Bandar Lampung, 2016)
The problem investigated in this study related to the ability of mathematics communication of the Seventh grade students at SMP Negeri 1 PadangCermin which is not optimal, therefore, the objective of this study is to investigate the influence of ARIAS (Assurance, Relevance, Interest,Assessment, Satisfaction) learning model in setting cooperative towards the the ability of mathematics communication. This study used experimental research. The population of this study was the students of the Seventh grade students at SMP Negeri 1 Padang Cermin. The sampe was taken from two classes, VII A as an experimental class and VII B as a control class, which consist of 30 students. The technique used to analyze the data was t-test. The research instruments used in this research was eassay test. From the calculation, it is obtained that thit = 7,72 from the distribution table of 5% daf t= 2,00, it is proven that thit > tdaf so it can be concluded that there is the influence of ARIAS (Assurance, Relevance, Interest, Assessment, Satisfaction) learning model in setting cooperative towards the the ability of mathematics communication at the students of the Seventh grade students at SMP Negeri 1 Padang Cermin 2015/2016.